Strain and cocaine-induced differential opioid gene expression may predispose Lewis but not Fischer rats to escalate cocaine self-administration - Valenza, Marta (Neuropharmacology, 2016)
The aim of the present study was to investigate alterations in gene expression of opioid system components induced by extended access (18 h) cocaine self-administration and to determine the impact of genetic background in the vulnerability to escalate cocaine intake. Comparing two inbred rat strains, we previously reported that Lewis rats progressively escalated cocaine consumption compared to Fischer rats, in a new translational model of intravenous cocaine self-administration, which included 14 sessions of 18-h operant sessions in which rats were allowed to select the cocaine unit dose to self-administer. We compare here Fischer and Lewis rats in the gene expression of endogenous opioid peptides (Pomc, Penk, Pdyn) and cognate receptors (Oprm, Oprk and Oprd) in reward-related brain regions, after exposure to either cocaine self-administration or yoked-saline, in the aforementioned translational paradigm. We performed a correlation analysis between the mRNA level, found in the Dorsal Striatum (DS), Nucleus accumbens (NAcc) shell and core respectively, and individual cocaine intake. Our findings show that the gene expression of all the aforementioned opioid genes exhibit strain-dependent differences in the DS, in absence of cocaine exposure. Also, different strain-specific cocaine-induced mRNA expression of Oprm and Oprk was found in DS. Only few differences were found in the ventral parts of the striatum. Moreover, gene expression level of Pdyn, Penk, Oprk, and Oprm in the DS was significantly correlated with cocaine intake only in Fischer rats. Overall, these data shed light on potential genetic differences which may predispose of subjects to initiate and escalate cocaine consumption.